The Effects of Transformational Leadership, Organizational Innovation, Work Stressors, and Creativity on Employee Performance in SMEs - Nasir, Jawaria; Ibrahim, Rashidah M.; Sarwar, Muhammad Arslan; Sarwar, Binesh; Al-Rahmi, Waleed Mugahed; Alturise, Fahad; Samed Al-Adwan, Ahmad; Uddin, Mueen (Frontiers in Psychology, 2022)
Purpose of the study: The significance of creativity and performance in the workplace has been illustrated on various occasions. This study aims to find out if there is a link between transformative leadership, organizational innovation, psychological issues such as hindrance and challenge stressors, and employee creativity and employee performance. There is still a lack of awareness of the factors that influence employee performance in small and medium businesses (SMEs) in Pakistan. Pakistan's SMEs have struggled to survive in their early years, with an initial failure rate of 90 percent to 95 percent. Methodology: The relationship between hindrance and challenge stressors, organizational innovation, transformational leadership, employee creativity, and their effect on overall employee performance is established through employing Structural Equation Modeling (SEM). In this study, constructs were developed from existing theories, hypotheses were generated, data collection procedures were implemented, and tests were conducted to prove the suggested hypothesis. The employees of SMEs are the research study's unit of analysis. Findings: The findings of this study demonstrated that challenge stressors, transformational leadership, and employee creativity all had positive and significant effects on employee performance. Originality/value: This is one of the first researches to study and extends existing understanding of psychological research in this manner and following correlations in a developing country, Pakistan: the links between transformational leadership and employees' perception of creativity and performance along with organizational innovation and work stressors. Based on theoretical considerations, a model is proposed, and hypotheses are established and explored. The findings of this study can help businesses increase employee performance by informing employee performance improvement methods. Business executives might learn more about how to engage and motivate employees to improve their performance.